Monitoring the Banggai Cardinalfish, an Endangered Restricted Range Endemic Species - Moore, Abigail; Ndobe, Samliok; Zamrud, Muhammad (Journal of Indonesian Coral Reefs, 2011)
In the marine reallm restricted range endemic species are rare. One such species which has attracted much attention is the Banggai cardinalfish (Pterapogon kauderni, Koumans 1933), often referred to as BCF, a coral reef associated fish endemic to shallow waters (0-5m) around the Banggai Archipelago, Indonesia. As in most of the Coral Triangle, these coastal waters are under heavy pressure from a variety of anthropogenic impacts. Traded as a marine ornamental, the IUCN Red-List places P. kauderni in the Endangered category with overexploitation and habitat degradation as the major threats. After the (unsuccessful) proposal for listing under CITES Appendix II in 2007, a national action plan (BCFAP) was developed and BCF conservation included in the Indonesian Coral Triangle Initiative National Plan of Action (CTI-NPOA). Monitoring is widely accepted as an integral part of effective management. The BCF-AP calls for biophysical and socio-economic monitoring of the Banggai cardinalfish trade, population and habitat to support the development of a sustainable ornamental fishery and ensure the conservation of the Banggai cardinalfish. Monitoring systems developed, activities undertaken and data produced are reviewed. Trends revealed by the data include a marked increase in compliance with current fish quarantine regulations, and other improvements in P. kauderni use patterns. Together with recent research, the data also reveal the need for an especial focus on key micro-habitat, Diadema urchins and sea anemones, which are under pressure from increasingly intensive harvesting. Monitoring systems are evaluated and suggestions for improving the usefulness and scope of monitoring activities are presented.